Relato de uma experiência de terreno de intervenção em Psicodinâmica do Trabalho (PDT) - Valérie Ganem (Universidade do Porto, 2011)
We aim to identify the methodological principles that seem to be crucial in a psychodynamics of work scenario, through a field experience, in order to avoid the risk of materialization that threatens all that adopt this subject. Next, we analyse the difficulties inherent to this type of intervention, such as the questions that remain unanswered associated to the prevention principle and to the status of these surveys.